Embedded sensing package for temporary bone cement spacers in infected total knee arthroplasty. (March 2021) - Lavdas, Michael K.; Willing, Ryan; Lanting, Brent A.; Teeter, Matthew G.
Abstract: The re-infection rate of total knee arthroplasty (TKA) after two stage revision (15%) remains high as it can be challenging to determine whether the infection has been fully cleared between the first and second stage procedures. Temporary embedded sensor systems could be a potential solution to indicate whether the infection has been cleared. In this study a telemetric sensor system to integrate with a bone cement spacer and measure knee joint temperature was designed and evaluated. The sensor package precision, accuracy, hysteresis, and thermal equilibrium were empirically determined. Cadaveric testing was performed with the sensor package implanted inside the femoral notch alongside a pre-formed femoral and tibial bone cement spacer. The limb was tested though 30, 000 cycles at 0.5 Hz under a 500 N load. Accuracy and precision of the sensing package were found to be ±0.24 °C and 0.09 °C respectively with negligible hysteresis. Thermal insulation caused by the implant itself was found to produce a thermal time constant of 263 ± 5 s, resulting in a 17 min rise time. Memory capacity enabled data logging every 20 s for a 6 week period before necessitating data transfer. Bluetooth was suitable for data transmission while the package was implanted. Following cyclic loading of the cadaveric specimen, imaging and debridement revealed no issues related to mechanical integrity of the bone cement spacer or encapsulated sensor package. While additional validation is required before use in patients, the concept of temporary embedded sensing technology to aid management of infection treatments is promising.